High-purity synthesis method of methyl 3-methoxypropionate
By using efficient catalysts and adsorbents in the synthesis process of methyl 3-methoxypropionate, the problems of high cost and low purity in the prior art are solved, and efficient and low-cost high purity synthesis is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202510241994.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-03
AI Technical Summary
In the prior art, the high-purity synthesis method of methyl 3-methoxypropionate has problems such as high cost, low product purity, and difficult to recover and utilize the catalyst.
Using metal layered hydroxide as a support, magnetic iron tetroxide is supported in situ, and nickel molybdate is grown in hydrothermal method to prepare a catalyst with high catalytic activity and easy recovery. At the same time, modified silicon oxide is used as the adsorbent to absorb heavy metal ions and organic matter in the raw material by supporting tannin acid and other active groups, thereby improving the purity of the product.
The high-purity synthesis of methyl 3-methoxypropionate is achieved, the catalyst is easy to be separated and recovered, the product yield is high, the by-product is few, and the cost is low, and it is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic synthesis, and in particular to a high-purity synthesis method of methyl 3-methoxypropionate. Background Art
[0002] Methyl 3-methoxypropionate (MMP) is a moderately volatile ether-ester environmentally friendly solvent. The ether-ester group, linear structure and propionyl group in the center of the molecule give it some special properties that other solvents do not have, such as strong solubility, strong polarity, strong hydrophilicity, etc. It is mainly used in the production of liquid crystal displays and photoresists as TFT-LCD photoresist thinners, photoresist removers, strippers, IC cleaning agents, photoresist removal buffers, etchant processes, and other chemicals requiring special specifications. It is also widely used as a solvent for the production of electronic materials. At present, some domestic chemical companies and research institutions have mastered the synthesis method and application technology of methyl 3-methoxy-propionate, but there are few reports in China as an environmentally friendly functional solvent for lithium battery manufacturing.
[0003] NMP (N-methylpyrrolidone) is classified as a CMR substance (Note: CMR is a triple carcinogen, meaning carcinogenic, mutagenic, and teratogenic). It is classified as a solvent for reproductive toxicants, meaning it is toxic to reproduction and may harm the fetus. Therefore, methyl 3-methoxypropionate is expected to completely or partially replace the existing mainstream solvent NMP as a supporting solvent for lithium battery positive electrode binders. Summary of the invention
[0004] The invention aims to provide a high-purity synthesis method of methyl 3-methoxypropionate. The preparation method is simple, efficient, low-cost and easy to realize industrial production. The catalyst is easy to separate and recycle, has high catalytic activity, high product yield and few by-products. The adsorbent is used for adsorbing heavy metal ions, colloids, organic matter and the like in the raw materials, thereby greatly improving the purity of the product and having broad application prospects.
[0005] The technical solution of the present invention is achieved in this way: The invention provides a high-purity synthesis method of methyl 3-methoxypropionate. The method comprises the following steps: uniformly mixing a catalyst, an adsorbent and methanol, heating, dropwise adding methyl acrylate, reacting by heat preservation and stirring, cooling to room temperature, separating the catalyst by a magnet, washing, drying and recycling, separating the adsorbent by filtering, washing, drying and recycling, and heating and fractionating the filtrate to obtain methyl 3-methoxypropionate.
[0006] As a further improvement of the present invention, the molar ratio of methanol to methyl acrylate is 1.1-1.4:1, the heating temperature is 50-60°C, the insulation stirring reaction time is 2-4h, the added amount of the catalyst is 0.5-1wt% of the total mass of the system, and the added amount of the adsorbent is 2-3wt% of the total mass of the system.
[0007] As a further improvement of the present invention, the preparation method of the catalyst is as follows: S1. Dissolve ferric chloride, aluminum chloride and magnesium chloride in water to obtain liquid A; use ammonia water as liquid B; ultrasonically disperse magnetic ferroferric oxide in water, heat, and simultaneously drop liquid A and liquid B, adjust the pH value of the solution, keep the solution warm and stir to react, age, filter, collect the precipitate, and obtain Fe3O4@FeAlMg-LDH; S2. Dissolve nickel nitrate and ammonium molybdate in water, add Fe3O4@FeAlMg-LDH, perform hydrothermal reaction, cool to room temperature, separate with a magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH; S3. Potassium nitrate and NiMoO4 / Fe3O4@FeAlMg-LDH were added into water, dispersed evenly by ultrasonication, dried, and calcined to obtain a catalyst.
[0008] As a further improvement of the present invention, the mass ratio of ferric chloride, aluminum chloride, magnesium chloride and magnetic ferrosoferric oxide in step S1 is 0.6-0.8:3-5:2-3:0.4-0.6, the heating temperature is 60-70°C, the pH value of the solution is adjusted to 9-10, the insulation stirring reaction time is 2-4h, and the aging time is 20-24h.
[0009] As a further improvement of the present invention, the mass ratio of nickel nitrate, ammonium molybdate and Fe3O4@FeAlMg-LDH in step S2 is 3-5:1:5-7, the temperature of the hydrothermal reaction is 140-160°C, and the time is 6-8h.
[0010] As a further improvement of the present invention, the mass ratio of potassium nitrate and NiMoO4 / Fe3O4@FeAlMg-LDH in step S3 is 2-3:10, the calcination temperature is 550-650°C, and the calcination time is 3-5h.
[0011] As a further improvement of the present invention, the preparation method of the adsorbent is as follows: T1. Adding silica powder to water, adding tannic acid and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified silica; T2. Add modified silica to water, add NHS and EDC, stir to activate, add silk fibroin peptide, stir to react, centrifuge, wash, and dry to obtain silk fibroin peptide@silica; T3. Add silk fibroin peptide@silicon oxide, phytic acid, β-cyclodextrin and sodium dihydrogen phosphate into water, perform hydrothermal reaction, centrifuge, add the product into alkaline solution, stir and react, centrifuge, wash and dry to obtain an adsorbent.
[0012] As a further improvement of the present invention, the average particle size of the silicon oxide powder in step T1 is 10-20 μm, the mass ratio of the silicon oxide powder tannic acid and the catalyst is 10:3-4:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 45-55° C., and the time is 2-4 hours.
[0013] As a further improvement of the present invention, the mass ratio of modified silica, NHS, EDC and silk fibroin peptide in step T2 is 10:3-4:2-3:7-10, the stirring activation time is 30-40 minutes, and the stirring reaction time is 5-7 hours.
[0014] As a further improvement of the present invention, the mass ratio of the silk fibroin peptide@silicon oxide, phytic acid, β-cyclodextrin, and sodium dihydrogen phosphate in step T3 is 10:4-6:5-7:1-2, the temperature of the hydrothermal reaction is 140-160°C, the time is 5-7h, the alkali solution is 10-15wt% NaOH or KOH solution, and the stirring reaction time is 1-2h.
[0015] The present invention has the following beneficial effects: The 3-methoxy-methyl propionate prepared by the invention is a colorless and transparent solvent, is an innovative ether ester functional solvent, is non-irritating to the skin, and is an environmentally friendly green solvent. The preparation method of the invention is simple, efficient, low in cost, and easy to realize industrial production. The catalyst is easy to separate and recycle, has high catalytic activity, high product yield, and few by-products. The adsorbent is used for adsorbing heavy metal ions, colloids, organic matter, etc. in the raw materials, thereby greatly improving the purity of the product and having broad application prospects.
[0016] The present invention prepares a catalyst, using metal layered hydroxide as a carrier, in-situ loading magnetic ferroferric oxide, so that the catalyst has good ferromagnetism, easy to achieve magnetic separation, so as to facilitate separation from an adsorbent, recovery and reuse, and in-situ growth of nickel molybdate by a hydrothermal method, the Fe3O4@FeAlMg-LDH carrier provides a large specific surface area and abundant catalytic active sites, so that the prepared NiMoO4 / Fe3O4@FeAlMg-LDH has a large reaction specific surface area, abundant active sites, and excellent electron transport performance. Finally, potassium nitrate is used as a precursor for impregnation loading on NiMoO4 / Fe3O4@FeAlMg-LDH, which has good reaction activity, and the active component has good firmness, is not easy to lose K, and can maintain high activity for a long time and multiple reactions.
[0017] The invention prepares an adsorbent, which uses silicon oxide as a carrier and carries tannic acid on the surface, so that the surface of the silicon oxide carries abundant carboxyl groups, thereby being easy to couple with silk protein peptides, thereby providing abundant hydroxyl groups and amino groups, and through bridging with phytic acid and beta-cyclodextrin, the surface of the adsorbent carries abundant active groups such as carboxyl groups, hydroxyl groups, amino groups, phosphate groups, etc., can have excellent adsorption and fixation energy for heavy metal ions, colloids, etc., and also has a large number of cavities, which has a good fixation effect on organic matter, thereby greatly purifying the raw materials, and the purity of the prepared 3-methoxypropionic acid methyl ester is significantly improved. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The average particle size of silicon oxide powder was 10-20 μm and was purchased from Hebei Ruihuang Metal Materials Co., Ltd.
[0020] Preparation Example 1 Preparation of Catalyst Here’s how: S1. Dissolve 0.6g ferric chloride, 3g aluminum chloride and 2g magnesium chloride in 100mL water to obtain liquid A; use 5wt% ammonia water as liquid B; add 0.4g magnetic ferroferric oxide to 100mL water, disperse it ultrasonically at 1000W for 10min, heat to 60℃, add liquid A and liquid B dropwise at the same time, adjust the solution pH to 9, keep warm and stir for 2h, age for 20h, filter and collect the precipitate to obtain Fe3O4@FeAlMg-LDH; S2. Dissolve 3g nickel nitrate and 1g ammonium molybdate in 100mL water, add 5g Fe3O4@FeAlMg-LDH, hydrothermally react at 140℃ for 6h, cool to room temperature, separate with a magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH; S3. Add 2 g potassium nitrate and 10 g NiMoO4 / Fe3O4@FeAlMg-LDH into 100 mL water, disperse under 1000 W ultrasonic wave for 15 min, dry, and calcine at 550 °C for 3 h to obtain a catalyst.
[0021] Preparation Example 2 Preparation of Catalyst Here’s how: S1. Dissolve 0.8g ferric chloride, 5g aluminum chloride and 3g magnesium chloride in 100mL water to obtain liquid A; use 7wt% ammonia water as liquid B; add 0.6g magnetic ferroferric oxide to 100mL water, ultrasonically disperse for 10min at 1000W, heat to 70℃, add liquid A and liquid B dropwise at the same time, adjust the solution pH to 10, keep warm and stir for 4h, age for 24h, filter and collect the precipitate to obtain Fe3O4@FeAlMg-LDH; S2. Dissolve 5g nickel nitrate and 1g ammonium molybdate in 100mL water, add 7g Fe3O4@FeAlMg-LDH, and perform hydrothermal reaction at 160℃ for 8h. Cool to room temperature, separate with a magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH. S3. Add 3 g potassium nitrate and 10 g NiMoO4 / Fe3O4@FeAlMg-LDH into 100 mL water, disperse under 1000 W ultrasonic wave for 15 min, dry, and calcine at 650 °C for 5 h to obtain a catalyst.
[0022] Preparation Example 3 Preparation of Catalyst Here’s how: S1. Dissolve 0.7g ferric chloride, 4g aluminum chloride and 2.5g magnesium chloride in 100mL water to obtain liquid A; use 6wt% ammonia water as liquid B; add 0.5g magnetic ferrosoferric oxide to 100mL water, disperse at 1000W ultrasonic for 10min, heat to 65℃, add liquid A and liquid B dropwise at the same time, adjust the solution pH to 9.5, keep warm and stir for 3h, age for 22h, filter and collect the precipitate to obtain Fe3O4@FeAlMg-LDH; S2. Dissolve 4g nickel nitrate and 1g ammonium molybdate in 100mL water, add 6g Fe3O4@FeAlMg-LDH, hydrothermally react at 150℃ for 7h, cool to room temperature, separate with a magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH; S3. Add 2.5 g potassium nitrate and 10 g NiMoO4 / Fe3O4@FeAlMg-LDH into 100 mL water, disperse under 1000 W ultrasonic wave for 15 min, dry, and calcine at 600 °C for 4 h to obtain a catalyst.
[0023] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0024] The details are as follows: S1. Dissolve 0.7g ferric chloride, 4g aluminum chloride and 2.5g magnesium chloride in 100mL water to obtain liquid A; use 6wt% ammonia water as liquid B; add 0.5g magnetic ferrosoferric oxide to 100mL water, disperse at 1000W ultrasonic for 10min, heat to 65℃, add liquid A and liquid B dropwise at the same time, adjust the solution pH to 9.5, keep warm and stir for 3h, age for 22h, filter and collect the precipitate to obtain Fe3O4@FeAlMg-LDH; S2. Add 2.5 g potassium nitrate and 10 g Fe3O4@FeAlMg-LDH into 100 mL water, disperse under 1000 W ultrasonic wave for 15 min, dry, and calcine at 600 °C for 4 h to obtain a catalyst.
[0025] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0026] The details are as follows: S1. Dissolve 0.7g ferric chloride, 4g aluminum chloride and 2.5g magnesium chloride in 100mL water to obtain liquid A; use 6wt% ammonia water as liquid B; add 0.5g magnetic ferrosoferric oxide to 100mL water, disperse at 1000W ultrasonic for 10min, heat to 65℃, add liquid A and liquid B dropwise at the same time, adjust the solution pH to 9.5, keep warm and stir for 3h, age for 22h, filter and collect the precipitate to obtain Fe3O4@FeAlMg-LDH; S2. Dissolve 4g nickel nitrate and 1g ammonium molybdate in 100mL water, add 6g Fe3O4@FeAlMg-LDH, and carry out hydrothermal reaction at 150℃ for 7h. Cool to room temperature, separate with a magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH, which is the catalyst.
[0027] Test Example 1 The specific surface area and pore structure of the catalysts prepared in Preparation Examples 1-3 of the present invention and Comparative Preparation Examples 1-2 were tested using an ASAP2400 static nitrogen adsorption instrument from Mircomeritics, Inc., USA. The results are shown in Table 1.
[0028] Table 1 Group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Preparation Example 1 605 0.578 Preparation Example 2 607 0.580 Preparation Example 3 610 0.584 Comparative Preparation Example 1 549 0.510 Comparative Preparation Example 2 568 0.535 It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have larger specific surface areas and pore volumes.
[0029] Preparation Example 4 Preparation of adsorbent Here’s how: T1. Add 10g of silica powder to 200mL of water, add 3g of tannic acid and 0.5g of catalyst, heat to 45°C, stir and react for 2h, centrifuge, wash and dry to obtain modified silica; The catalyst is a Tris-HCl solution with a pH of 8.5; T2. 10 g of modified silica was added to 200 mL of water, 3 g of NHS and 2 g of EDC were added, and the mixture was stirred for activation for 30 min. 7 g of silk fibroin peptide was added, and the mixture was stirred for reaction for 5 h. The mixture was centrifuged, washed, and dried to obtain silk fibroin peptide@silica. T3. Add 10g silk fibroin peptide@silica, 4g phytic acid, 5g β-cyclodextrin, and 1g sodium dihydrogen phosphate into 200mL water, perform hydrothermal reaction at 140℃ for 5h, centrifuge, add the product into 10wt% NaOH solution, stir and react for 1h, centrifuge, wash, and dry to obtain an adsorbent.
[0030] Preparation Example 5 Preparation of adsorbent Here’s how: T1. Add 10g of silica powder to 200mL of water, add 4g of tannic acid and 1g of catalyst, heat to 55°C, stir and react for 4h, centrifuge, wash and dry to obtain modified silica; The catalyst is a Tris-HCl solution with a pH of 9.5; T2. 10 g of modified silica was added to 200 mL of water, 4 g of NHS and 3 g of EDC were added, and the mixture was stirred and activated for 40 min. 10 g of silk fibroin peptide was added, and the mixture was stirred and reacted for 7 h. The mixture was centrifuged, washed, and dried to obtain silk fibroin peptide@silica. T3. Add 10g silk fibroin peptide@silica, 6g phytic acid, 7g β-cyclodextrin, and 2g sodium dihydrogen phosphate into 200mL water, perform hydrothermal reaction at 160℃ for 7h, centrifuge, add the product into 15wt% KOH solution, stir and react for 2h, centrifuge, wash, and dry to obtain an adsorbent.
[0031] Preparation Example 6 Preparation of adsorbent Here’s how: T1. Add 10g of silica powder to 200mL of water, add 3.5g of tannic acid and 0.7g of catalyst, heat to 50°C, stir and react for 3h, centrifuge, wash and dry to obtain modified silica; The catalyst is a Tris-HCl solution with a pH of 9; T2. 10 g of modified silica was added to 200 mL of water, 3.5 g of NHS and 2.4 g of EDC were added, and the mixture was stirred for activation for 35 min. 8.6 g of silk fibroin peptide was added, and the mixture was stirred for reaction for 6 h. The mixture was centrifuged, washed, and dried to obtain silk fibroin peptide@silica. T3. Add 10g silk fibroin peptide@silica, 5g phytic acid, 6g β-cyclodextrin, and 1.4g sodium dihydrogen phosphate into 200mL water, perform hydrothermal reaction at 150℃ for 6h, centrifuge, add the product into 12wt% NaOH solution, stir and react for 1.5h, centrifuge, wash, and dry to obtain an adsorbent.
[0032] Comparative Preparation Example 3 Compared with Preparation Example 6, the difference is that step T3 is not performed.
[0033] The details are as follows: T1. Add 10g of silica powder to 200mL of water, add 3.5g of tannic acid and 0.7g of catalyst, heat to 50°C, stir and react for 3h, centrifuge, wash and dry to obtain modified silica; The catalyst is a Tris-HCl solution with a pH of 9; T2. Add 10g of modified silica to 200mL of water, add 3.5g of NHS and 2.4g of EDC, stir and activate for 35min, add 8.6g of silk fibroin peptide, stir and react for 6h, centrifuge, wash and dry to obtain silk fibroin peptide@silica, which is the adsorbent.
[0034] Comparative Preparation Example 4 Compared with Preparation Example 6, the difference is that steps T2 and T3 are not performed.
[0035] The details are as follows: T1. Add 10g of silica powder to 200mL of water, add 3.5g of tannic acid and 0.7g of catalyst, heat to 50°C, stir and react for 3h, centrifuge, wash and dry to obtain modified silica, which is the adsorbent; The catalyst is a Tris-HCl solution with a pH of 9.
[0036] Test Example 2 The specific surface area and pore structure of the adsorbents prepared in Preparation Examples 4-6 of the present invention and Comparative Preparation Examples 2-4 were tested using an ASAP2400 static nitrogen adsorption instrument from Mircomeritics, Inc., USA. The results are shown in Table 2.
[0037] Table 2 Group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Preparation Example 4 657 0.612 Preparation Example 5 653 0.610 Preparation Example 6 660 0.615 Comparative Preparation Example 3 603 0.587 Comparative Preparation Example 4 537 0.502 It can be seen from the above table that the adsorbents prepared in Preparation Examples 4-6 of the present invention have larger specific surface areas and pore volumes.
[0038] Example 1 The present embodiment provides a high-purity synthesis method of methyl 3-methoxypropionate. The catalyst prepared in Preparation Example 1, the adsorbent prepared in Preparation Example 4 and methanol are uniformly mixed, wherein the amount of the catalyst added is 0.5wt% of the total mass of the system, and the amount of the adsorbent added is 2wt% of the total mass of the system. The mixture is heated to 50°C, methyl acrylate is added dropwise, and the molar ratio of methanol to methyl acrylate is 1.1:1. The mixture is stirred and kept warm for 2 hours, cooled to room temperature, the catalyst is separated by a magnet, washed, dried, and recycled, the adsorbent is separated by filtration, washed, dried, and recycled, and the filtrate is heated and fractionated to obtain methyl 3-methoxypropionate.
[0039] Example 2 The present embodiment provides a high-purity synthesis method of methyl 3-methoxypropionate. The catalyst prepared in Preparation Example 2, the adsorbent prepared in Preparation Example 5 and methanol are uniformly mixed, wherein the amount of the catalyst added is 1wt% of the total mass of the system, and the amount of the adsorbent added is 3wt% of the total mass of the system. The mixture is heated to 60°C, methyl acrylate is added dropwise, and the molar ratio of methanol to methyl acrylate is 1.4:1. The mixture is stirred and kept warm for 4 hours, cooled to room temperature, the catalyst is separated by a magnet, washed, dried, and recycled, the adsorbent is separated by filtration, washed, dried, and recycled, and the filtrate is heated and fractionated to obtain methyl 3-methoxypropionate.
[0040] Example 3 The present embodiment provides a high-purity synthesis method of methyl 3-methoxypropionate, wherein the catalyst prepared in Preparation Example 3, the adsorbent prepared in Preparation Example 6 and methanol are uniformly mixed, wherein the amount of the catalyst added is 0.7wt% of the total mass of the system, and the amount of the adsorbent added is 2.5wt% of the total mass of the system; the mixture is heated to 55°C, methyl acrylate is added dropwise, and the molar ratio of methanol to methyl acrylate is 1.25:1; the mixture is stirred and kept warm for 3 hours, cooled to room temperature, the catalyst is separated by a magnet, washed, dried, and recycled, the adsorbent is separated by filtration, washed, dried, and recycled, and the filtrate is heated and fractionated to obtain methyl 3-methoxypropionate.
[0041] Comparative Example 1 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 1.
[0042] Comparative Example 2 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 2.
[0043] Comparative Example 3 Compared with Example 3, the difference is that the adsorbent is prepared by Comparative Preparation Example 3.
[0044] Comparative Example 4 Compared with Example 3, the difference is that the adsorbent is prepared by Comparative Preparation Example 4.
[0045] Comparative Example 5 Compared with Example 3, the difference is that no adsorbent is added.
[0046] Test Example 3 The reactions in Examples 1-3 and Comparative Examples 1-3 were evaluated and the results are shown in Table 3.
[0047] Table 3 Group Yield of methyl 3-methoxypropionate (%) Purity of methyl 3-methoxypropionate (%) Example 1 99.992 >99.999 Example 2 99.990 >99.999 Example 3 99.997 >99.999 Comparative Example 1 96.124 99.015 Comparative Example 2 91.295 99.242 Comparative Example 3 99.912 97.455 Comparative Example 4 99.906 95.782 Comparative Example 5 99.824 89.045 It can be seen from the above table that the methods in Examples 1-3 of the present invention can obtain high-purity methyl 3-methoxypropionate with a high reaction yield.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-purity synthesis method of methyl 3-methoxypropionate, characterized in that: The catalyst, adsorbent and methanol are mixed evenly, heated, methyl acrylate is added dropwise, the mixture is stirred and kept warm for reaction, cooled to room temperature, the catalyst is separated by a magnet, washed, dried and recycled, the adsorbent is separated by filtration, washed, dried and recycled, the filtrate is heated and fractionated to obtain methyl 3-methoxypropionate.
2. The synthesis method according to claim 1, characterized in that The molar ratio of methanol to methyl acrylate is 1.1-1.4:1, the heating temperature is 50-60° C., the heat preservation and stirring reaction time is 2-4 hours, the added amount of the catalyst is 0.5-1wt% of the total mass of the system, and the added amount of the adsorbent is 2-3wt% of the total mass of the system.
3. The high-purity synthesis method according to claim 1, characterized in that: The preparation method of the catalyst is as follows: S1. Dissolve ferric chloride, aluminum chloride and magnesium chloride in water to obtain liquid A; use ammonia water as liquid B; ultrasonically disperse magnetic ferroferric oxide in water, heat, and simultaneously drop liquid A and liquid B, adjust the pH value of the solution, keep the solution warm and stir to react, age, filter, collect the precipitate, and obtain Fe3O4@FeAlMg-LDH; S2. Dissolve nickel nitrate and ammonium molybdate in water, add Fe3O4@FeAlMg-LDH, perform hydrothermal reaction, cool to room temperature, separate by magnet, wash, and dry to obtain NiMoO4 / Fe3O4@FeAlMg-LDH; S3. Potassium nitrate and NiMoO4 / Fe3O4@FeAlMg-LDH were added into water, dispersed evenly by ultrasonication, dried, and calcined to obtain a catalyst.
4. The high-purity synthesis method according to claim 3, characterized in that: In step S1, the mass ratio of ferric chloride, aluminum chloride, magnesium chloride and magnetic ferrosoferric oxide is 0.6-0.8:3-5:2-3:0.4-0.6, the heating temperature is 60-70°C, the pH value of the solution is adjusted to 9-10, the insulation stirring reaction time is 2-4h, and the aging time is 20-24h.
5. The high-purity synthesis method according to claim 3, characterized in that: In step S2, the mass ratio of nickel nitrate, ammonium molybdate and Fe3O4@FeAlMg-LDH is 3-5:1:5-7, the temperature of the hydrothermal reaction is 140-160°C, and the time is 6-8h.
6. The high-purity synthesis method according to claim 3, characterized in that: In step S3, the mass ratio of potassium nitrate to NiMoO4 / Fe3O4@FeAlMg-LDH is 2-3:10, the calcination temperature is 550-650°C, and the calcination time is 3-5h.
7. The high-purity synthesis method according to claim 1, characterized in that: The preparation method of the adsorbent is as follows: T1. Adding silica powder to water, adding tannic acid and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified silica; T2. Add modified silica to water, add NHS and EDC, stir to activate, add silk fibroin peptide, stir to react, centrifuge, wash, and dry to obtain silk fibroin peptide@silica; T3. Add silk fibroin peptide@silicon oxide, phytic acid, β-cyclodextrin and sodium dihydrogen phosphate into water, perform hydrothermal reaction, centrifuge, add the product into alkaline solution, stir and react, centrifuge, wash and dry to obtain an adsorbent.
8. The high-purity synthesis method according to claim 7, characterized in that: The average particle size of the silicon oxide powder in step T1 is 10-20 μm, the mass ratio of the silicon oxide powder tannic acid and the catalyst is 10:3-4:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 45-55° C., and the time is 2-4 hours.
9. The high-purity synthesis method according to claim 7, characterized in that: In step T2, the mass ratio of modified silica, NHS, EDC and silk fibroin peptide is 10:3-4:2-3:7-10, the stirring activation time is 30-40 minutes, and the stirring reaction time is 5-7 hours.
10. The high-purity synthesis method according to claim 7, characterized in that: In step T3, the mass ratio of silk fibroin peptide@silicon oxide, phytic acid, β-cyclodextrin, and sodium dihydrogen phosphate is 10:4-6:5-7:1-2, the temperature of the hydrothermal reaction is 140-160°C, the time is 5-7h, the alkali solution is 10-15wt% NaOH or KOH solution, and the stirring reaction time is 1-2h.
Citation Information
Patent Citations
Dye wastewater adsorbent based on core-shell structure and preparation method thereof
CN107096491A
Silver-loaded mesoporous silica microspheres as well as preparation method and application thereof
CN115044105A
Catalyst, preparation method thereof and method for preparing methyl 3-methoxypropionate by catalyzing methanol and methyl acrylate with catalyst
CN116116402A
Synthetic method of ethyl 3-ethoxypropionate
CN118619829A
High-purity methyl 3-methoxypropionate filtering device
CN222239182U